Parental migration and self‐efficacy among rural‐origin adolescents in China: Patterns and mechanisms. Issue 2 (9th December 2022) - Wen, Ming; Wang, Weidong; Ahmmad, Zobayer; Jin, Lei
Abstract: Large‐scale rural‐to‐urban migration has shaped the socialization contexts of rural adolescents in China and can potentially impact their developmental outcomes. In this study, using data from the first wave of the China Education Panel Study collected in 2013, we focused on self‐efficacy, an important but under‐studied facet of noncognitive development, and assessed how it was influenced by family migration status. We also explored the mediating role of family and school resources. We compared three groups of rural‐origin adolescents with different family migration statuses: rural left‐behind children (LBC), rural not‐left‐behind children (NLBC), and rural‐to‐urban migrant children (MC). Structural equation modeling was performed to estimate the main effects of rural‐origin groups on self‐efficacy and the mediating effects of family income, family social capital, and school social capital for the significant group effects on self‐efficacy. We found similar levels of self‐efficacy among MC and NLBC, who in turn, exhibited greater self‐efficacy than LBC. Discrepancies in family and school resources mediated the self‐efficacy gaps between LBC and their MC and NLBC counterparts. Notably, when their disadvantages in family and school resources were controlled for, LBC were more efficacious than MC and NLBC, indicating LBC's resilience and the potential for promoting self‐efficacy in LBC by providing adequate resources and support.